Utilization of Sikkam Bark Extract on Iron Corrosion Inhibition in H2SO4 Solution: A Study on the Effectiveness of Iron Material Protection - Sri Adelila Sari; Zukyandus Rivaldi Situmorang; Ribka Angelia Sinaga; Uci Gresia Tarigan; Ho Soon Min (JIPI (Jurnal IPA & Pembelajaran IPA), 2025)
Corrosion represents a major challenge in industrial systems due to its detrimental impact on the performance, safety, and durability of metallic materials, particularly carbon steel in acidic environments. This study evaluated the effectiveness of sikkam bark extract (Bischofia javanica Blume) as an eco-friendly corrosion inhibitor for carbon steel in sulfuric acid (H2SO4) solution. The extract, obtained via maceration using 96% ethanol, was applied in various concentrations to 1–5% H₂SO₄ media, with specimens immersed for 24 hours at 30°C. The corrosion behavior was analyzed through gravimetric measurements, pH monitoring, and surface morphology characterization using scanning electron microscopy (SEM). The highest inhibition efficiency of 95.56% was achieved at 5% inhibitor concentration in 5% H2SO4, accompanied by a significant reduction in mass loss and corrosion rate. The increase in solution pH after immersion confirmed the neutralization of H⁺ ions and the formation of a stable passive film composed of tannin–Fe complexes on the steel surface. SEM analysis further revealed a compact and continuous organic layer responsible for suppressing ion diffusion and electron transfer. These results demonstrate that sikkam bark extract functions as a highly efficient and sustainable green inhibitor, offering strong potential for corrosion mitigation in acidic environments relevant to petrochemical and industrial applications.